2012
DOI: 10.1177/1745691611424750
|View full text |Cite
|
Sign up to set email alerts
|

Linking Process and Outcome in the Study of Emotion and Aging

Abstract: Current theory and research on emotion and aging suggests that (1) older adults report more positive affective experience (more happiness) than younger adults; (2) older adults attend to and remember emotionally-valenced stimuli differently than younger adults (i.e., they show age-related positivity effects in attention and memory); and (3) the reason that older adults have more positive affective experience is because the positivity effects they display serve as emotion regulatory strategies. It is suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 89 publications
10
145
1
2
Order By: Relevance
“…Isaacowitz & Blanchard-Fields, 2012), this indicates that older adults' attentional deployment does not merely reflect mood, but that it may serve emotion regulation. Thus, this study replicates previous results on the link between sad mood increases and larger attentional patterns reflecting a positivity effect (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isaacowitz & Blanchard-Fields, 2012), this indicates that older adults' attentional deployment does not merely reflect mood, but that it may serve emotion regulation. Thus, this study replicates previous results on the link between sad mood increases and larger attentional patterns reflecting a positivity effect (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Reed et al, 2014;Urry & Gross, 2010). Given that the positivity effect in attention is thought to reflect an emotion regulation strategy, it has been proposed that it should become more pronounced under conditions where emotion regulation is needed, such as during increased negative mood (Isaacowitz & Blanchard-Fields, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to young adults, older individuals show increased functional connectivity between the amygdala and the prefrontal cortex (PFC) and a decrease in amygdala-hippocampal coupling during the encoding and retrieval of negative versus neutral information (Murty et al, 2009). It has been suggested that the age-related differences in the recruitment of frontal brain areas during exposure to negative stimuli indicate an emotionregulation attempt (an assumption for which there is as yet only limited evidence; see Isaacowitz & Blanchard-Fields, 2012), with the PFC being employed to minimize amygdala activation and dampen responses to negative stimuli (St. Jacques, Bessette-Symons, & Cabeza, 2009). The downregulation of negative affect appears to be more successful for material requiring elaborate processing (i.e., low-arousal stimuli; Dolcos, Katsumi, & Dixon, GLUCOSE AND POSITIVITY EFFECTS IN OLD AGE 4 2014; Kensinger, 2008) than for high-arousal stimuli, which are thought to be processed in a more automatic fashion (Kensinger, 2004).…”
Section: Food For Happy Thought: Glucose Protects Age-related Positivmentioning
confidence: 99%
“…Isaacowitz and Blanchard-Fields (2012) have recently cautioned against drawing parallels between age-related positivity effects and emotional regulation without specific evidence in support of a connection. Given the importance of this topic, especially in consideration of potential implications for prevention and treatment of affective disorders, further studies are warranted.…”
Section: Cognitive Reserve and Positivity Effect 15mentioning
confidence: 99%